Long‐term clinical outcome of rotational atherectomy followed by drug‐eluting stent implantation in complex calcified coronary lesions. Issue 2 (2nd May 2012) - Abdel‐Wahab, Mohamed; Baev, Radoy; Dieker, Patrick; Kassner, Guido; Khattab, Ahmed A.; Toelg, Ralph; Sulimov, Dmitriy; Geist, Volker; Richardt, Gert
<x xml:space="preserve">Abstract</x> Objectives To assess long‐term outcome after rotational atherectomy (RA) is followed by drug‐eluting stent (DES) implantation in complex calcified coronary lesions. Background RA can favorably modify heavily calcified coronary lesions, but long‐term outcome is poor when it is used as a stand‐alone therapy or combined with bare‐metal stents. DES have reduced rates of restenosis in a wide range of patient and lesion subsets, but little information is available on long‐term clinical outcome when RA is followed by DES implantation (Rota‐DES) in complex calcified lesions. Methods and Results Two hundred and five patients with de novo complex calcified coronary lesions treated with Rota‐DES were analyzed. Mean age was 69.7 ± 9.3 years, 63 patients (31%) had diabetes mellitus and 21 patients (10%) had chronic renal failure. Total stent length/patient was 32 mm. The majority of patients were treated with paclitaxel‐eluting stents (64%) or sirolimus‐eluting stents (30%). Angiographic success rate was 98%. The incidence of in‐hospital major adverse cardiac events (MACE), defined as death, myocardial infarction (MI), and target vessel revascularization (TVR), was 4.4%. Long‐term follow‐up was available for 188 patients (92%). At a median follow‐up period of 15 months (range, 1–84), the cumulative incidence of MACE (Kaplan–Meier estimate) was 17.7%. Death occurred in 4.4%, MI in 3.4%, TVR in 9.9%, and target lesion revascularization (TLR) in 6.8%. One definite (0.5%) and one probable (0.5%) stent thrombosis were observed. In a multivariate analysis, low ejection fraction (<40%) was the only independent predictor of MACE, and both age and diabetes were independent predictors of TLR. Conclusion This study represents the largest European data set of patients treated with RA in the DES era. RA followed by DES implantation in calcified coronary lesions appears to be feasible and effective, with a high rate of procedural success and low incidence of TLR and MACE at long term considering this complex patient and lesion subset. © 2012 Wiley Periodicals, Inc.